Banking Secrecy in Comparative Perspective: Remarks on the Background of French and Czech Law - Mariański, Michał; Bartes, Richard (Review of European and Comparative Law, 2025)
Banking secrecy is an institution that is well known in many European legal systems, as its regulation is an important element of the creation of a legal framework for the protection of individual data of national citizens. The method of regulating the described secrecy is always referring to some type of compromise between the public and the private interest of the economic actors in the given national system. The purpose of this article, in which the authors use the dogmatic, historicaldescriptive method and, above all, the comparative method, will be to compare the way and scope of introducing the definition of banking secrecy in French and Czech law. The comparative analysis will allow for the drawing of a number of conclusions in the discussed scope, including the response to the question if despite European Union regulations, we can observe some important differences in that field at the national level. Another issue is related to the technological neutrality of the language that is being used, as an element that could give the response about the compatibility of national regulations to current technological evolution. The different ways of regulating banking secrecy in France and in the Czech Republic, presented in this paper, can be an interesting element of a broader discussion of the changes that may be needed in other national systems of EU member states.